2018
DOI: 10.1111/pace.13388
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of cardiac resynchronization therapy using left ventricular quadripolar leads

Abstract: Quadripolar leads achieve similar CRT outcomes as bipolar LV leads but with a higher implant success rate and fewer procedure-related complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…NYHA class improvement was more with quadripolar lead at six months, and this was in concordance with previous studies by Yang et al. (2018) [ 6 ] (62.9 Quad vs 51.4 BiP; p 0.04) and Earth et al. (2019) [ 20 ] (QP LV leads (OR = 2.30; 95% CI 1.37–3.85; p 0.002).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…NYHA class improvement was more with quadripolar lead at six months, and this was in concordance with previous studies by Yang et al. (2018) [ 6 ] (62.9 Quad vs 51.4 BiP; p 0.04) and Earth et al. (2019) [ 20 ] (QP LV leads (OR = 2.30; 95% CI 1.37–3.85; p 0.002).…”
Section: Discussionsupporting
confidence: 91%
“…(2019) [ 20 ] (QP LV leads (OR = 2.30; 95% CI 1.37–3.85; p 0.002). Taking ≥1 NHYA class improvement as a criterion of response [ 6 , 7 , 12 , 20 ] CRT responder at six months were more in the quadripolar group (87.09% vs 67.74% in BiP; p 0.04). Greater NYHA improvement can be attributed to better LVEF improvement at six months (Δ9.39 ± 1.48% in Quad vs Δ 5.61 ± 1.05% in BiP; p 0.004) and extensive use of diuretics (100% in both the study groups) which was higher when compared to diuretic use in MIRACLE (91%) [ 11 ], RAFT (84.7%) [ 13 ] and MADIT CRT (75.7%) [ 17 ] trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, prospective randomized clinical trials assessing the mortality rates with IS‐4 and IS‐1 systems with long‐term FU are lacking and may suffer from confounding effects due to concomitant heart failure therapy regimen changes over time. One randomized controlled trial with a 6‐month FU time 10 and other studies with up to 12 months of FU time showed no significant difference in all‐cause mortality rate 9,11,20–24 . Interestingly, other retrospective studies with long‐term FU (>3 years) or large patient groups showed lower mortality for patients implanted with IS‐4 LV leads 12–13,25 .…”
Section: Discussionmentioning
confidence: 98%
“…One randomized controlled trial with a 6-month FU time 10 and other studies with up to 12 months of FU time showed no significant difference in all-cause mortality rate. 9,11,[20][21][22][23][24] Interestingly, other retrospective studies with long-term FU (>3 years) or large patient groups showed lower mortality for patients implanted with IS-4 LV leads. [12][13]25 By contrast, the all-cause mortality rate of the IS-4 and the IS-1 patient group did not show significant difference at a minimum of 3 years FU in our cohort.…”
Section: Mortalitymentioning
confidence: 91%